Towards responsible cord blood banking models - Rebulla, P. (Cell Prolif, 2011)
On 31 May 2010, 14 072 567 bone marrow/apheresis donors registered in 44 countries and 426 501 cord blood units banked in 26 countries for public use were available to treat candidates to haemopoietic stem cell transplant lacking a family related compatible donor. Despite these impressive numbers, additional efforts are required to ensure that all patients, including those from ethnic minorities, can promptly find a suitable donor. Governments, clinicians, scientists, patients and stakeholders should share the responsibility to develop haemopoietic stem cell donation and cord blood banking models able to fully match all patient needs. In this regard, current scientific evidence and prevalent opinions among expert clinicians support solidaristic cord blood donation for public use against the alternative option of commercial autologous cord blood storage.